THE ROLE OF MICROALGAE IN CARBON CAPTURE AND LIPID ACCUMULATION: A MINI REVIEW - Eva Musifa (Universitas Islam Sumatera Utara, 2026)
The increasing concentration of carbon dioxide (CO₂) in the atmosphere is a major factor driving global climate change. Therefore, effective, sustainable, and environmentally friendly mitigation strategies are needed. Microalgae have emerged as a promising biological solution due to their high photosynthetic capacity to absorb CO₂ and convert it into biomass. This review article aims to examine the role of microalgae in carbon mitigation, focusing on the CO₂ absorption mechanism, the efficiency of the cultivation system, and its relationship to lipid production as a biofuel feedstock. Microalgae utilize the Carbon Concentrating Mechanism (CCM) to increase carbon fixation efficiency, even at low CO₂ concentrations. The absorbed carbon is then converted through the Calvin cycle into organic compounds that serve as precursors for lipid biosynthesis. Microalgae tend to increase lipid accumulation in the form of triacylglycerols (TAGs), which have the potential to be converted into biodiesel. In addition to contributing to carbon sequestration, microalgae also have economic value through the production of biofuels and other high-value compounds, thus supporting the concept of a circular economy. With the right technological development, microalgae have the potential to become an integrated solution for carbon mitigation and renewable energy supply in the future.